2019
DOI: 10.4018/978-1-5225-7180-3.ch029
|View full text |Cite
|
Sign up to set email alerts
|

ESG and Financial Performance

Abstract: Non-financial information such as environmental, social, governance (ESG) issues is becoming as much important as financial data. This study investigated the empirical relationship between Thomson Reuters Environmental Social Governance (ESG) Combined Score and performance of S&P 500 firms with eleven years of data from between 2006 and 2016. The study confirmed unidirectional positive and significant relation between ESG Combined Score and ROA, suggesting that improvements in ESG score have positive impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Azmi et al (2021) analyze the link between ESG activity and bank value and conclude that ESG activity benefits cash flows and efficiency. Aybars et al ’s (2019) study finds that the ESGS affects Tobin’s Q and that firms with a higher Tobin’s Q are less sensitive to ESG problems. The importance of firm size as a control variable has long been understood.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 84%
See 1 more Smart Citation
“…Azmi et al (2021) analyze the link between ESG activity and bank value and conclude that ESG activity benefits cash flows and efficiency. Aybars et al ’s (2019) study finds that the ESGS affects Tobin’s Q and that firms with a higher Tobin’s Q are less sensitive to ESG problems. The importance of firm size as a control variable has long been understood.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 84%
“…Nirino et al (2021), Nekhili et al (2019) and Azmi et al (2021) stated a significant association between ESG performance and market performance. Similarly, Aybars et al (2019) found a link between ESG and investor attitudes. According to Tamayo-Torres et al (2018), investors use ESG data for predicted financial performance.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 85%
“…Subsequently, investors starting to consider timely and accurate non-financial terms such as ESG parameters factors in their investment decisions. Listed firms started to integrate ESG activities as one of the strategic direction and being effectively disclosed those activities to the investors and stakeholders (Aybars et al, 2019). This being supported by the stakeholder theory (Freeman, 1984) that holds firm should also focus on the comprehensive need of stakeholders such as the workforces, dealers, clienteles, societies, financial institutions, regulatory agents and others; and not only towards firm's profit maximizations.…”
Section: Problem Statementmentioning
confidence: 99%
“…Sustainable business models adopt a multi-criteria character in the realisation of corporate objectives, where sustainability is not the only determinant of development (integration of objectives [9] of the value bundling process). Highlighted in the literature as a tool for assessing the effectiveness of green growth-oriented activities is the ESG, focusing attention on [10]:…”
Section: Introductionmentioning
confidence: 99%